EVALUASI PROGRAM PEMBELAJARAN BAHASA INGGRIS DENGAN MODEL CIPP DI INSTITUT AGAMA KRISTEN NEGERI KUPANG - Yandry Diana Dethan; Mariyanti Adu; Fransiska Y Nggeong; Jegi Taneo (Program Studi PGSD Universitas Flores, 2024)
The English language skills of Christian Education Study Program students are still low. Therefore, this research aims to determine the effectiveness of English learning program. This research uses a qualititative approach with an evaluation model that focuses on context, input, ptocess, and product. The data in this research comes from interview of two English lecturers and six students who have taken English course in the semester one of 2022/2023 and documentation (curriculum, lesson plans, and journal class). The data collection techniques used were: interview and documentation. The result of the research showed that the implemementation of English learning in Christian Education Study Program had not been effective although the average of each class is above of 70. It could be seen: 1) evaluation context describes that the learning program has not been able to answer the program objectives; 2) evaluation input reveals that the study materials contains in the curriculum are still too general, teaching materials are not yet available to students, and the infrastructure cannot fully support the English language learning process; and 3) evaluation process asserts that the leaning tools are prepared after learning, learning process is carried using the old method, and the form of assignments is not yet project/ problem solving based.